Good doctor and bad doctor: A qualitative study of first year medical students’ views on professionalism - Kumar, Dinesh; Murugan, Magi; Prasad, Bhavani; Devi, Rema (Research and Humanities in Medical Education, 2018)
Introduction: Professionalism is emphasized in medical school curricula; however, there is lack of consensus on what constitutes professionalism. This study aimed at exploring incoming medical studentsâ€™ views on professionalism through student constructs of the ’good’ and the ’bad’ doctor. Methods: After Institutional Ethics Committee approval and informed consent, all (n=150) incoming first-year medical students were asked their reasons for pursuing medicine and their perceptions of the attributes of a ’good’ and a ’bad’ doctor. Following the anonymous survey, we used nominal group discussions to achieve consensus about the desirable and undesirable attributes that emerged from student responses. After an iterative theming process, a list of themes were derived from the written reflections of students. Results: Competence, communication, and professionalism were some of the perceived attributes of a good doctor, while being money-minded, having inadequate knowledge or competence, and rudeness were some of the reported attributes of a bad doctor. We identified six themes for the question ’Why pursue medicine?’: affective / humanitarian response; thoughts about further pursuits; fulfillment; traits of the profession; ability to contribute to society; and personal experiences. Conclusion: Our results suggest that first year medical students have a fair idea of the behavior expected from a good doctor. Formal reflection on these expectations may hone the concept of professionalism for new entrants into the profession. The teaching of professionalism could incorporate such activities to allow students and educators to articulate and explore tensions between what is taught and what is experienced as they progress through the profession.